2017
DOI: 10.1111/tra.12502
|View full text |Cite
|
Sign up to set email alerts
|

Transport of the alpha subunit of the voltage gated L‐type calcium channel through the sarcoplasmic reticulum occurs prior to localization to triads and requires the beta subunit but not Stac3 in skeletal muscles

Abstract: Contraction of skeletal muscle is initiated by excitation-contraction (EC) coupling during which membrane voltage is transduced to intracellular Ca2+ release. EC coupling requires dihydropyridine receptors (DHPR) located at triads, which are junctions between the transverse (T) tubule and SR membranes, that sense membrane depolarization in the T tubule membrane. Reduced EC coupling is associated with ageing, and disruptions of EC coupling result in congenital myopathies for which there are few therapies. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Stac regulation of Ca V 1 modifies multiple aspects of Ca V 1 function. For Ca V 1.1, stac3 enhances plasmalemmal trafficking ( Linsley et al, 2017b ; Niu et al, 2018 ; Polster et al, 2015 ; Wong King Yuen et al, 2017 ; Wu et al, 2018 ), and promotes conformational coupling to RyR ( Linsley et al, 2017a ; Polster et al, 2016 ). For Ca V 1.2, however, stac1-3 isoforms slow inactivation ( Campiglio et al, 2018 ; Polster et al, 2015 ; Wong King Yuen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stac regulation of Ca V 1 modifies multiple aspects of Ca V 1 function. For Ca V 1.1, stac3 enhances plasmalemmal trafficking ( Linsley et al, 2017b ; Niu et al, 2018 ; Polster et al, 2015 ; Wong King Yuen et al, 2017 ; Wu et al, 2018 ), and promotes conformational coupling to RyR ( Linsley et al, 2017a ; Polster et al, 2016 ). For Ca V 1.2, however, stac1-3 isoforms slow inactivation ( Campiglio et al, 2018 ; Polster et al, 2015 ; Wong King Yuen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, key domains within stac relevant for Ca V modulation remain controversial. Previous studies have identified the dual SH3 and C1 domains to be critical for stac effect on trafficking and coupling to RyR ( Campiglio and Flucher, 2017 ; Linsley et al, 2017a ; Linsley et al, 2017b ; Polster et al, 2016 ), while the C1 has been proposed to be critical for modifying Ca V 1 CDI ( Campiglio et al, 2018 ; Wong King Yuen et al, 2017 ). Our findings instead suggest that the U-domain in the stac2 linker region is sufficient to fully recapitulate reduction in Ca V 1 CDI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stac3 also regulates EC coupling in murine skeletal muscles ( Nelson et al, 2013 ) and murine muscle development ( Ge et al, 2014 ; Cong et al, 2016 ). In zebrafish skeletal muscles Stac3 colocalizes with DHPR and RyR and regulates DHPR levels, stability and functionality, including the voltage response of DHPRs but not trafficking of DHPRs ( Linsley et al, 2017a , b ). Stac3 appears not to be required for normal levels or functionality of RyRs, however.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies from the same group and others, however reported that in Stac3 KO myotubes, the failure of ECC was not a result of a trafficking defect of Ca V 1.1. Albeit at reduced levels, Ca V 1.1 was present on the plasma membrane but was not able to generate ECC Ca 2+ currents (Linsley, Hsu, Wang, & Kuwada, ; Polster, Nelson, Olson, & Beam, ). The ECC was only restored after expression of the WT Stac3, demonstrating that Stac3 is important for the functional link between Ca V 1.1 and RyR1 (Linsley, Hsu, Wang, et al., ; Polster et al., ).…”
Section: Introductionmentioning
confidence: 99%